THE FIBONACCI SPIRAL MOTIFS ON BATIK DESIGN - Wan Norliza Wan Bakar; Junaidi Awang; Mohd Saipuddin Mohd Hasbullah; Muslim Bin Ismail (Journal of Islamic, Social, Economics and Development, 2022)
Fibonacci Sequence is a series of numbers in which each given number is the addition of the two numbers before it. Fibonacci numbers are strongly related to the golden ratio and implies that the ratio of two consecutive Fibonacci numbers tends to approach the golden ratio, which is a proportion roughly 1.16, as the number of term increases. Fibonacci Sequence has been called as ‘the nature of secret code ‘or ‘the nature universal’ and we can instantly recognize how this sequence works in nature like an underlying universal grid. In Geometry, Fibonacci Sequence can be illustrated as the Fibonacci Spiral motifs as the squares representing the width of numbers in the sequence. The sequence fit nicely together forming the spiral, this paper aims to discuss on the process of designing four new motifs of batik design based on the Fibonacci spiral motifs.